Establishing and Managing Development Networks in Africa: Perspectives on the African Virtual Library and Information Network (Avlin) - Alemna, A.A.; Adjei, Emmanuel (Ghana Library Journal, 2007)
In times like this when libraries are facing problems with access and acquisition of materials, networking becomes very important. This paper discusses issues relating to networking in libraries with particular reference to the African Virtual Library and Information Network (AVLIN). The paper focuses on the goals and objectives of AVLIN; achievements and potential barriers; and the way forward for AVLIN. The paper also stresses the need for the sustenance of AVLIN in order to alleviate the problems of information provision in Africa.